PERANCANGAN SISTEM INFORMASI AKADEMIK DAN KEMAHASISWAAN BERBASIS WEB (STUDI KASUS: LLDIKTI WILAYAH V) - Yoko Khomarudin Habiburochman; Deden Hardan Gutama; Andri Pramuntadi; Dita Danianti (Program Studi Informatika Universitas Teknologi Sumbawa, 2025)
LLDIKTI Region V is responsible for facilitating higher education implementation in Yogyakarta region, but currently lacks a specific platform to display academic and student affairs data to the public. SINTA, research, community service, KIP Kuliah, RPL, PKM, MBKM, and student achievement data are stored in separate internal platforms accessible only to certain administrators. This research aims to design and develop a web-based academic and student information system named